2011
DOI: 10.1021/cs200326m
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Selective Catalytic Reduction (SCR) of NOx with n-Octane Using Solvent-Free Mechanochemically Prepared Ag/Al2O3 Catalysts

Abstract: Low-temperature (<200 °C) hydrocarbon selective catalytic reduction of NO x has been achieved for the first time in the absence of hydrogen using a solvent-free mechanochemically prepared Ag/Al2O3 catalyst. Catalysts prepared by this ball-milling method show a remarkable increase in activity for the reduction of nitrogen oxides with octane by lowering the light-off temperature by up to 150 °C compared with a state-of-the-art 2 wt % Ag/Al2O3 catalyst prepared by wet impregnation. The best catalyst prepared fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 34 publications
1
50
0
Order By: Relevance
“…The wet impregnation method, which has always been considered as the best way to prepare Ag/ Al 2 O 3 catalysts, 17,26 was also tested in this study. It was confirmed that wet impregnation produced the best catalysts among all samples in the reduction of NOx.…”
Section: Resultsmentioning
confidence: 99%
“…The wet impregnation method, which has always been considered as the best way to prepare Ag/ Al 2 O 3 catalysts, 17,26 was also tested in this study. It was confirmed that wet impregnation produced the best catalysts among all samples in the reduction of NOx.…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies have shown that the HC-SCR reaction to be greatly enhanced by the addition of hydrogen to the feed [29][30][31][32][33][34][35][36]46] and this has also been shown to be the case for the ball milled catalysts [9]. In fact, the ball milled catalyst in the presence of hydrogen has resulted in the lowest light off temperature reported, to date, under thermally activated conditions (165 • C) although lower temperature activity has been observed under non-thermal plasma conditions [47].…”
Section: Activity Testsmentioning
confidence: 96%
“…[9] For the purposes of comparison we use the light off temperature, which we define as the temperature for 50% NO x conversion. The silver catalyst prepared by wet-impregnation has a light off temperature of 390 • C whereas the ball milled catalyst has a light off temperature of only about 240 • C. In an attempt to gain greater understanding on how the ball milling affects the activity of the catalyst the effect of the ball milling parameters was studied.…”
Section: Activity Testsmentioning
confidence: 99%
See 2 more Smart Citations